Danielle Walker's against all grain. Meals made simple : gluten-free, dairy-free, and paleo recipes to make anytime - Walker, Danielle (Chef) (Walker, Danielle (Chef). Against all grain., 2014)
Meals Made Simple answers the age-old question: "What's for dinner?" Danielle Walker takes the guesswork out of meal planning with eight weeks' worth of dinner ideas, complete with full shopping lists and recipes for using up leftovers. Whether we're moms, students, or business owners, at the end of the day we all want fresh, home-cooked meals that are easy to prepare. And we want lots of variety. Preparing real foods can be time-consuming and monotonous, but Danielle brings both simplicity and creativity to the everyday meal with an enthusiasm for flavors and textures that are often lacking in easy weeknight dishes. Meals Made Simple includes a variety of slow cooker, one-pot, and thirty-minute meals, as well as ways to create entirely new dishes from leftovers. The vibrant flavors and colors in these grain-free dishes, like slow-cooked Pork Ragu, Beef Stroganoff, Peruvian-Style Chicken, Chicken and Rice Casserole, and Barbecue Salmon with Peach Salsa, add delight to any meal and put an end to all those nights of mundane grilled chicken and steamed vegetables. Even the desserts are quick to make, should a craving or a last-minute celebration arise.